PENINGKATAN AKTIVITAS DAN KETUNTASAN BELAJAR KOMPETENSI DASAR MENDESKRIPSIKAN RUMAH SEHAT MATA PELAJARAN ILMU PENGETAHUAN SOSIAL MENGGUNAKAN MODEL PEMBELAJARAN KONSTRUKTIVISME BAGI PESERTA DIDIK KELAS I DI SEKOLAH DASAR NEGERI 1 SUKARAME BANDAR LAMPUNG - Inawati, Inawati (Lentera: Jurnal Ilmiah Kependidikan, 2016)
The objective of this research is to improve the students’ learning outcomes in the learning materials on social civic subject at the students in SD Negeri 1 Bandar Lampung using constructivism learning model. This study is classroom action research. The participants come from the students in SDN 1 Bandar Lampung. From the description above data it can be seen that the effective use of the constructivism learning models can encourage the development of thinking learners first class of SD Negeri 1 Sukarame. It can be seen from the spirit of everyday learners in the learning process and the results of the assessment obtained by the students during the study.